Pituitary Adenylate Cyclase Activating Peptide and Post-traumatic Stress Disorder: From Bench to Bedside - Riser, Manessa; Norrholm, Seth Davin (Frontiers in Psychiatry, 2022)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide with isoforms consisting of either 27 or 38 amino acids. PACAP is encoded by the adenylate cyclase activating peptide gene, ADCYAP1, in humans and the highly conserved corresponding rodent gene, Adcyap1. PACAP is known to regulate cellular stress responses in mammals. PACAP is robustly expressed in both central nervous system (CNS) and peripheral tissues. The activity of PACAP and its selective receptor, PAC1-R, has been characterized within the hypothalamic-pituitary-adrenal (HPA) axis and autonomic division of the peripheral nervous system, two critical neurobiological systems mediating responses to stressors and threats. Findings from previous translational, empirical studies imply PACAP regulation in autonomic functions and high expressions of PACAP and PAC1 receptor in hypothalamic and limbic structures, underlying its critical role in learning and memory, as well as emotion and fear processing. The current review summarizes recent findings supporting a role of PACAP/PAC1-R regulation in key brain areas that mediate adaptive behavioral and neurobiological responses to environmental stressors and maladaptive reactions to stress including the development of fear and anxiety disorders.